Level of Education as the Determinant Factor of Obstetric Outpatients’ Knowledge about Intra Uterine Device in Kramat Jati Public Health Center - Dhika Prabu (Indonesian Journal of Obstetrics and Gynecology, 2012)
Objective: To know the main factor affecting the knowledge of obstetric outpatients about intra uterine device (IUD). Method: This is across sectional study involving 106 subjects who were selected by a consecutive random sampling in obstetric outpatients clinic, Kramat Jati Public Health Center, Jakarta. Data were obtained from guided questionnaire. There are several dependent variables, including the knowledge level of respondents toward IUD. Meanwhile, there are also independent variables, including education level, job, number of children, history of contraception use, and sources of information. The knowledge score >60% is considered good. Afterwards, the data was evaluated with multivariate analysis with binary logistic regression. Result: The study found association between the rate of knowledge with the level of education (p=0.015) and history of contraceptive usage (p=0.022). In multivariate analysis, it appeared that education level was the determinant factor, with the rate of low knowledge 2.6 times higher in the low education group. Conclusion: Level of education are the determinant factor of obstetric outpatients’ knowledge about intra uterine device in Kramat Jati Public Health Center. [Indones J Obstet Gynecol 2012; 36-1:43-7] Keywords: IUD, knowledge, level of education